Impaired episodic memory in PTSD patients — A meta-analysis of 47 studies - Petzold, Maria; Bunzeck, Nico (Frontiers in Psychiatry, 2022)
Episodic memory impairments beyond the traumatic event might be a characteristic hallmark of post-traumatic stress disorder (PTSD). Although several studies support such a claim, empirical findings are inconsistent. Therefore, we performed a random-effects meta-analysis including data from a total of 47 studies and 3062 subjects. As main finding, we can show that PTSD patients show episodic memory deficits compared to all controls. This effect was significantly stronger for PTSD vs non-traumatized healthy controls as compared to PTSD vs traumatized controls without PTSD. Finally, episodic memory impairments in PTSD were most pronounced in verbal memory tests as compared to non-verbal memory tests. Our results provide new evidence that PTSD is characterized by impaired episodic long-term memory beyond the traumatic event, and these deficits are particularly pronounced in verbal memory. We will discuss our findings in the context of physiological, psychological and trauma related memory models. From a broader perspective, our findings have implications for the treatment of PTSD by suggesting that the assessment and, if necessary, training of memory deficits should necessarily be included as part of diagnostics and psychotherapeutic treatment.